An analysis of spatiotemporal changes and local governance toward the management of geographically isolated wetlands (Paulista Peripheral Depression, Brazil) - Junqueira, Deise Aparecida [UNESP]; Conciani, Dhemerson E.; Furlan, Lucas Moreira [UNESP]; Rizzieri, Rafael Moraes [UNESP]; Rosolen, Vania [UNESP] (Springer Nature, 2024)
The large diversity of ecosystem services provided by natural wetlands has been underestimated by decision-making authorities in Brazil, posing a threat to sustainable development. The intensive land use practices and increased water usage in the country are the main forces driving the degradation and depletion of small wetlands. The aim of this study was to assess the spatiotemporal changes in geographically isolated wetlands (GIWs) in the Paulista Peripheral Depression in São Paulo State, considering the intensification of land use and land cover (LULC) and the role of local governance in protecting water resources in these environments. Remote sensing imagery and climate data were utilized to analyze the spatial‒temporal changes in GIWs. The effectiveness of local governance policies in addressing wetland protection concerns was also evaluated. The findings indicate that the intensification of LULC has negative impacts on GIWs, leading to their depletion or degradation. Additionally, GIWs are outside the scope of regulatory protection at the federal, state, and local levels. This lack of protection contributes to the vulnerability of wetland resources, poses risks to local ecological benefits, and exacerbates social-environmental issues such as water scarcity.
Keywords: Environmental policies; Isolated wetland; LULC; Territorial planning